Penafsiran Hukum Terhadap Pasal 156a Kitab Undang-Undang Hukum Pidana Tentang Tindak Pidana Penodaan Agama - Mursalin, Adinda Faradilla; Ismansyah, Ismansyah; Yoserwan, Yoserwan (Nagari Law Review, 2024)
The criminal offense of religious defamation, regulated under Article 156a of the Indonesian Criminal Code, often triggers social and political issues due to varying interpretations, leading to debates and criminalization. This research discusses a notable case of religious defamation in Indonesia, specifically Verdict Number 1612/Pid.B/2018.Pn.Mdn involving the defendant, Meliana. In this verdict, the court found the defendant guilty of insulting Islam concerning the volume of the call to prayer (adhan) in her neighborhood. Her actions provoked public anger, leading to serious legal consequences. Therefore, this study aims to analyze and provide an in-depth interpretation to address ambiguities in the article's formulation concerning the boundaries of “hostility,” “misuse,” and “defamation.”The research focuses on three main questions: (1) What is the legal interpretation of the criminal offense of religious defamation under the Law on Religious Defamation? (2) How is the concept of religious defamation in Article 156a of the Criminal Code legally interpreted? and (3) How did the judge interpret the criminal offense of religious defamation in Medan District Court Verdict Number 1612/Pid.B/2018/Pn.Mdn? This study adopts a normative research method, focusing on the written rules, principles, and norms within a legal system and analyzing laws, regulations, jurisprudence, and legal doctrines to solve legal issues. The research findings indicate the need to review Article 156a of the Criminal Code to better align it with societal developments. The verdict discussed in this study demonstrates that the criminal sanctions imposed were inconsistent with the substantive law in Article 156a of the Criminal Code. The sanctions included administrative and criminal penalties, highlighting the dual-track system in Law Number 1/PNPS of 1965 and Article 156a of the Criminal Code. Therefore, a more specific legal interpretation is needed to ensure the fair application of Human Rights Principles.